ANALISIS YURIDIS TERHADAP PENERAPAN PRINSIP INDEMNITY DAN INSURABLE INTEREST PADA ASURANSI KEBAKARAN DI PT. ASURANSI TOKIO MARINE - Zulkifli, Suhaila; Stefanie, Stefanie; Philip, Margareth Christiana; Purba, Josua Hasiholan (Legal Standing : Jurnal Ilmu Hukum, 2022)
Fire Insurance protects against the danger of property loss or damage. Parties with an interest in the insured object accept the risk of loss. Indemnity (or the principle of loss) plays a role in ensuring equitable compensation. Subrogation will apply against the insured to ensure that the insurance policy runs properly and without loss between the insurer and the insured. The goal of this study is to discuss and explain the Indemnity Principles and Insurable Interest in relation with Fire Insurance. The descriptive qualitative method was employed in the research. Primary and secondary sources of data were gathered. Data analysis techniques included data collection, data reduction, data presentation, and data verification. The study's findings show that PT. Tokio Marine merely recovers the insured's financial condition to its pre-incident state. PT. Tokio Marine will not face risk adjustments as a result of an occurrence because the company only accepts risks that are uncertain and occur suddenly. Subrogation does not occur when the insurer pays the insured a balanced loss (indemnity principle). However, if the insurance covers only a portion of the loss, the subrogation principle applies.